The Chemistry of the Actinide and Transactinide Elements (3rd ed., Volumes 1-5) - Morss, L.R; Edelstein, Norman M.; Fuger, Jean (Springer Netherlands : Imprint: Springer, 2006)
The ?rst edition of this work (The Chemistry of the Actinide Elements by J. J. Katz and G. T. Seaborg) was published in 1957, nearly a half century ago. Although the chemical properties of thorium and uranium had been studied for over a century, and those of actinium and protactinium for over ?fty years, all of the chemical properties of neptunium and heavier elements as well as a great deal of uranium chemistry had been discovered since 1940. In fact, the concept that these elements were members of an "actinide" series was ?rst enunciated in 1944. In this book of 500 pages the chemical properties of the ?rst transuranium elements (neptunium, plutonium, and americium) were described in great detail but the last two actinide elements (nobelium and lawrencium) remained to be discovered. It is not an exaggeration to say that The Chemistry of the Actinide Elements expounded a relatively new branch of chemistry. The second edition was published in 1986, by which time all of the actinide elements had been synthesized and chemically characterized, at least to some extent. At this time the chemistry of the actinide elements had reached maturity.